Improving students' high order thinking skills through the application of the bridging analogy learning model - Ghina Ansely; Achi Rinaldi; Fredi Ganda Putra (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
Higher Order Thinking Skills (HOTS) are high-level thinking skills that include analytical, evaluative, and creative abilities. HOTS is essential in 21st-century education, where students are expected not only to recall information but also to think critically and creatively in facing various challenges. This study aims to determine the improvement of students' HOTS through the application of the Bridging Analogy learning model. The research design employed a quasi-experimental approach with one experimental class and one control class. The instruments used in this study were a HOTS test for Matrix material and a student learning activity questionnaire. Research data were analyzed using statistical analysis with SPSS. The ANCOVA results showed that the Bridging Analogy learning model significantly influenced students' HOTS. The data analysis also revealed that the average HOTS score of students in the experimental class (84.73) was higher than that of the control class, which used conventional learning (55). These findings indicate that the implementation of the Bridging Analogy learning model effectively enhances students' HOTS compared to conventional learning. This research contributes to the development of innovative learning models that support the improvement of students' higher-order thinking skills in mathematics education.